2020
DOI: 10.1088/2053-1591/ab7ac3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TiN inclusions on the fracture mechanism of 20CrMnTi steel with lath martensite

Abstract: This study aims to investigate the effect of TiN inclusions on the fracture mechanism of 20CrMnTi steel with martensite. Size of martensite packets, blocks and TiN inclusions were characterized, and the room-temperature tensile properties, impact toughness and fracture toughness were tested of 20CrMnTi steel quenched at different temperatures. The effects of TiN inclusions on the impact toughness and fracture toughness were investigated according to the Hall-Petch relationship. The results show that, TiN inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Two obvious deep cracks were present on the TiN inclusion, which indicates that the micron-scale TiN inclusions were broken and then separated from the matrix, leading to cleavage fracture. As previously reported [8,9], micron-sized (Ti, Nb)N/TiN particles can cause cleavage fracture, resulting in toughness decrease. Figure 6 shows SEM images of the fiber zone in the longitudinal tensile samples, which included both fine and large dimples, cleavage and quasi-cleavage surfaces, and numerous secondary cracks at the fracture surface [20].…”
Section: Fractographysupporting
confidence: 67%
See 3 more Smart Citations
“…Two obvious deep cracks were present on the TiN inclusion, which indicates that the micron-scale TiN inclusions were broken and then separated from the matrix, leading to cleavage fracture. As previously reported [8,9], micron-sized (Ti, Nb)N/TiN particles can cause cleavage fracture, resulting in toughness decrease. Figure 6 shows SEM images of the fiber zone in the longitudinal tensile samples, which included both fine and large dimples, cleavage and quasi-cleavage surfaces, and numerous secondary cracks at the fracture surface [20].…”
Section: Fractographysupporting
confidence: 67%
“…The maximum sizes of the TiN inclusions at 1/2 thickn and 1/4 thickness were 21.2 and 13.2 μm, respectively. TiN inclusions with a size lar than 5 μm at 1/2 thickness and 1/4 thickness were 105.5 and 34 number/cm 2 , respective According to previous studies [9,11,19], TiN inclusions with a size larger than 5 μm m induce cleavage fracture, leading to poor mechanical properties of steel plates. This w also related to the lower plasticity observed at 1/2 thickness compared with 1/4 thickne Figure 4 shows the size distribution of the TiN inclusions at 1/4 and 1/2 thickness of the plate.…”
Section: Microstructural Featuresmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, titanium may also affect the mechanical properties of the final product [2,3]. However, earlier investigations have demonstrated the formation of Ti-based inclusions, such as TiN and Ti 2 O 3 , in steels and their potentially detrimental effect on the steel properties [4,5]. Furthermore, numerous studies [6][7][8] have shown that the presence of TiN or Ti 2 O 3 inclusions generated during steelmaking or in final steel products could occur as a mixture with other detrimental oxide inclusion phases.…”
Section: Introductionmentioning
confidence: 99%